Modern treatment approaches for patients with IV stage of non-small cell lung cancer - Kadzhoian, А. V. (Zaporozhye Medical Journal, 2013)
Introduction. Lung cancer is currently the most common malignancy (1.6 million new cases annually), after non-melanoma skin cancer and the leading cause of cancer-related deaths (1.4 million annually). In Ukraine IV stage of the disease is diagnosed approximately in 27% of patients before their treatment. Chemotherapy, targeted therapy, radiation therapy and surgery are today the main treatment methods for patients with stage IV non-small cell lung cancer (NSCLC) depending on clinical circumstances. Despite significant progress in the treatment of NSCLC a slight improvement in survival has been noted during the last decade. The aim of this scientific review was to present modern treatment methods for patients with stage IV of non-small cell lung cancer (chemotherapy, radiation therapy, targeted therapy, surgery, hormone therapy, immunotherapy). For patients with a preserved performance status (0-2 points by ECOG), double agent platinum based therapy extends survival, improves quality of life, and reduces disease-related symptoms. The addition of a third cytotoxic agent increases toxicity without any clinical benefit. Customizing treatment based on histology and molecular typing has become the standard of care. Epidermal growth factor receptor (EGFR) genotyping and pathology subtyping should be considered routine in new diagnoses of metastatic NSCLC. Treatment options for those with somatic EGFR activating mutations include gefitinib until progression, followed by standard chemotherapy. Second-line chemotherapy is offered to a selected subgroup of patients upon progression and may include pemetrexed in non-squamous histology and docetaxel or erlotinib (or both) in all histologies. Currently, only erlotinib is offered as a third-line option in unselected NSCLC patients after failure of first- and second-line chemotherapy. A paradigm shift in favor of maintenance therapy for patients with advanced stage disease has gained strength from recent data. Radiation therapy for metastatic NSCLC plays a leading role in the control of bone and / or brain metastases’ symptoms. Surgery has limited value in the treatment of patients with metastatic NSCLC and includes primary tumor or distant metastases resection (including stereotactic radiosurgery in case of their cerebral localization). However, the question about the criteria of patients’ selection for such treatment and predictors of its successful outcome is still open because of scarcity and fragmentation of these data. One of the promising new directions in treatment of patients with stage IV NSCLC is hormonal treatment (the inclusion of antiestrogens to standard chemotherapy regimens). Another innovative strategy that may improve overall survival, with reduced toxicity compared with conventional cytotoxic chemotherapy, is the use of therapeutic cancer vaccines (vaccines made from a gene-modified virus may help the body build an effective immune response to kill tumor cells). ConclusionTreatment of patients with metastatic non-small cell lung cancer remains an urgent problem in modern oncology. Despite the improvements in care and number of therapeutic agents available, the survival for patients with IV stage of NSCLC remains modest. Novel approaches are required and participation in clinical trials should be encouraged. Key words: non-small cell lung cancer, chemotherapy, radiation therapy, targeted therapy, surgery.